LOYALTY PROGRAMMES AT - Human, Lezánne (My University, 2011)
The financial services industry is becoming increasingly competitive, resulting in higher customer churn and lower profitability. Well-structured loyalty programmes can play a key role in retaining profitable customers and driving profitable behaviour in those customers. Loyalty programmes in South African financial institutions have been launched with varying degrees of success, requiring an understanding of why a loyalty programme is needed and how it should be structured to achieve its objectives. In-depth interviews at a case site – the eBucks programme of FirstRand – were conducted. It was found that eBucks was implemented to increase profitability through driving profitable behaviour and retaining profitable customers, as well as through cross-selling and providing differentiation. The programme follows a ‘promotional currency’ structure and is multi-partner in nature. It reflects its unique environment and is specifically designed to ensure value to members and a competitive advantage against other loyalty programmes. Strong top leadership support adds an important dimension. The research should be of value to financial institutions debating the implementation or discontinuation of their loyalty programmes.
MBA - WBS
Keywords: Loyalty programmes; Financial institutions